1983
DOI: 10.1007/bf02498727
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prophylaxis for thrombosis on heterotopic ossification following total hip joint replacement

Abstract: The effect of prophylaxis for thrombosis on heterotopic ossification was investigated using 216 total hip joint endoprostheses implanted between 1976 and 1978. During this period a random comparative study of low dose heparin and oxyphenbutazone/acetylsalycilic acid was carried out. The rate of ossification in the 216 hip joints was 17.6%, and was about average for the values specified in literature on this subject. Heterotopic ossification occurred in 30.1% of the 103 hip joints treated with heparin, whilst t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A total of more than 400 study reports were reviewed. From these reports, 218 studies were confirmed as eligible 9,10,13,15−226 and the remainder were excluded. The principal reasons for the exclusion of studies were the absence of information about the incidence of heterotopic bone formation or about the number of participants or hips, 7,14 , 227−279 the conduct of other surgical procedures (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…A total of more than 400 study reports were reviewed. From these reports, 218 studies were confirmed as eligible 9,10,13,15−226 and the remainder were excluded. The principal reasons for the exclusion of studies were the absence of information about the incidence of heterotopic bone formation or about the number of participants or hips, 7,14 , 227−279 the conduct of other surgical procedures (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…We were not able to deduce a predisposition to heterotopic ossification in one or other sex as has been reported [11,17,30]. A possible reason could be that our patients were not preselected as in other series [5,40] in which patients were used who had an increased predisposition to heterotopic ossification.…”
Section: Discussionmentioning
confidence: 50%
“…Various methods of treatment have been used to try to prevents its occurrence. Those most often used are various medications [8,17,22,35,41,42,47,48,49] or local radiotherapy [5,11,28,30]. Radiotherapy has been shown to be effective and there had been a trend to smaller doses in recent years [3].…”
Section: Introductionmentioning
confidence: 99%
“… 14 First, we excluded 2 quasi-randomized trials. 57 , 58 Second, we introduced DNGSE, which was not analyzed by Fransen and Neal. 14 By analyzing DGSE, we found that the risk of gastrointestinal side effects was increased 30.4% by NSAIDs, which was similar to the results of Fransen and Neal.…”
Section: Discussionmentioning
confidence: 99%